Kegiatan Komunikasi Dalam Tradisi Nyawer Pada Pesta Pernikahan Adat Sunda - Muhammad Saepul Ulum; Mira Renata (Program Studi Hubungan Masyarakat Politeknik LP3I, 2023)
This study aims to describe the communication activities in the Nyawer tradition in Garut during Sundanese traditional weddings. This study discusses the communicative activities seen in communicative situations, events, and communicative behavior. This is a qualitative research method for ethnographic research on communication theory and symbolic interaction. The topic of his research is that some people happen when they sign the marriage contract. There are as many as traditional Sundanese, and all the reporters including 5 people. The sampling technique for the purpose of selecting information is used. The data collection techniques are in-depth interviews, non-participant observation, documentation, research, libraries and online data search. Data validity testing technology by increasing endurance, triangulation, discussions with colleagues, friends and members. The results showed that when the nyawer ceremony was held outside the building, the families of the bride and groom, the communication sawsman, make-up and the communication of the invited guests were involved. Communication Activities The nyawer ceremony is a special form of celebration, namely a traditional event that lasts 30 minutes and is held after the ceremony, while communication activities are traditional activities. Marriage customs and appear in the form of non-verbal behavior, including rice, turmeric, coins, flowers, candy, and areca nut.